Trust-driven job scheduling heuristics for computing grid - ZHANG Wei-zhe1; LIU Xin-ran2; YUN Xiao-chun1; ZHANG Hong-li1; HU Ming-zeng1; LIU Kai-peng1 (Tongxin xuebao)
Currently existing grid scheduling algorithms largely ignore the impact of trust mechanism,which made their applicability in a realistic environment rather doubtful.Based on the grid trust model and trust utilization functions,a trust-driven grid job scheduling problem was proposed.Trust-driven Min-min and Sufferage job scheduling heuristics were presented,which were extended based on traditional job scheduling strategies.The algorithms were evaluated with large scale simulation.Simulation result demonstrates trust-driven heuristics perform better than time-driven heuristic on average trust utility and total trust utility.